Problems and Solutions in Modern Healthcare Systems: A Comprehensive Review - Zhyvotovska, Liliia; Kozar, Yrii; Mirzebasov, Maksym; Bilohur, Vlada; Zozuliak, Vadym (Interacción y Perspectiva, 2024)
Public health care is one of the most important areas of state development, as it ensures the effective functioning of the state itself, its economic development, defense capability, and an adequate level of service and labor productivity. The purpose of the article is to outline a comprehensive analysis of the challenges faced by the three main healthcare systems - public, insurance and private - along with potential solutions to address these challenges. The author used general scientific methods of analysis, synthesis, generalization, abstraction, as well as systemic and functional methods of researching this problem. The unique challenges of each system are discussed, such as cost and accessibility, access to care, quality differences, and technological progress. In searching for solutions, the article emphasizes the importance of interdisciplinary collaboration, regulatory reforms, and innovative approaches to improve the efficiency, accessibility, and affordability of health care. By analyzing and understanding the strengths and limitations of each system, those interested in studying this area can gain comprehensive information on developing effective policies to improve health care delivery and promote the overall well-being of the population.